PENGARUH PENGUASAAN PEMUAIAN TERHADAP HASIL BELAJAR FISIKA SISWA MATERI POKOK KALOR KELAS VII SMP NEGERI - Palma Juanta (JURNAL PhysEdu (PHYSICS EDUCATION), 2020)
This aims to ascertain wheter or not any significant effect between mastery of the expansition to learning research fisika of topic the heat in SMP Negeri 1 Hutabargot. Population numbered 56 people, and samples were taken with cluster sampling were 56 people. The method and data collection using multiple choice test. The data obtained were processed two stages, namely descriptive analysis to see a picture of these two variables and using statistical test using correlation “r” product moment and to see whether there is a significant effect between the two variables used ttest. The result of analysis of the data obtained an averagr of variable x=72,14 and variable y=74,64, tcount=3,10 dan ttable=1,68 then tcountgreater than ttabel (3,10 > 1,68).